An Analysis of Students' Gramatical Error in Using Passive Voice at Grade Ten of SMA Persada Bandar Lampung 2014 - Ildhias Pratiwi Putri (Bandar Lampung University, 2015)
The purpose of this research was to analyze students’ grammatical error in using passive voice at grade ten in SMA Persada Bandar Lampung 2014. The data were collected by incorporating test to measure the students’ error in using passive voice based on surface strategy taxonomy. They did the structure tests that were a set of Indonesian sentences to be translated into English.Error analysis is a technique of analyzing, classifying, and describing the noticeable errors made by the students in learning process. Surface strategy highlights the way surface structures is altered. There are four types of error based on Surface Strategy Taxonomy: omission, addition, misformation and misordering. From 25 students, 436 total error were found that are classified into 4 types of error. They are 120 ommision error or 27,52 % (TOM : TE X 100 %), 19 addition error or 4,35 % ( TAD : TE X 100 %), 249 misformation error or 57,11 % (TMF : TE X100 %) and 48 misordering or 11,00 % (TMO : TE X 100%).Results indicate that of all types of errors on Surface Strategy Taxonomy we found the most dominant error was misformation and the least dominant error was addition. Therefore, it is recommended that students are required to improve their grammar understanding by studying passive voice sentence more deeply.